Analysis of an intense O3 pollution episode on the Atlantic coast of the Iberian Peninsula using photochemical modeling: characterization of transport pathways and accumulation processes - E. Torre-Pascual; G. Gangoiti; A. Rodríguez-García; E. Sáez de Cámara; J. Ferreira; C. Gama; M. C. Gómez; I. Zuazo; J. A. García; M. de Blas (Atmospheric Chemistry and Physics, 2024)
A tropospheric O3 pollution episode over the Atlantic coast of the Iberian Peninsula during 2–6 August 2018 has been analyzed. The episode was characterized by a permanent wind shear throughout the entire period, making the observed ozone surface distribution especially difficult to explain. A new methodology is described to analyze upper-level atmospheric parameters, such as temperature, wind direction, wind speed, and O3 concentrations, added to the traditional use of surface parameters, using the Weather Research and Forecasting (WRF) and Comprehensive Air Quality Model with Extensions (CAMx) models as well as available surface and upper-air observations. Results indicate that the episode was characterized by a first phase of a sudden increase in O3 concentrations produced by fumigation and inter-regional transport processes within the Iberian Peninsula, followed by continental O3 transport from Europe to the Atlantic coast. An Atlantic front produced the dissipation of the episode, generating an “ozone front” accompanying the cold front passage across the region.